Pretreatment gamma‐glutamyl transferase predicts mortality in patients with chronic hepatitis B treated with nucleotide/nucleoside analogs - Tyng‐Yuan Jang; Po‐Cheng Liang; Dae Won Jun; Jang Han Jung; Hidenori Toyoda; Chih‐Wen Wang; Man‐Fung Yuen; Ka Shing Cheung; Satoshi Yasuda; Sung Eun Kim; Eileen L. Yoon; Jihyun An; et al. (Kaohsiung Journal of Medical Sciences, 2024)
Abstract Elevated serum gamma‐glutamyl transferase (GGT) levels are associated with chronic hepatitis B (CHB)‐related hepatocellular carcinoma. However, their role in predicting mortality in patients with CHB treated with nucleotide/nucleoside analogs (NAs) remains elusive. Altogether, 2843 patients with CHB treated with NAs were recruited from a multinational cohort. Serum GGT levels before and 6 months (Month‐6) after initiating NAs were measured to explore their association with all‐cause, liver‐related, and non‐liver‐related mortality. The annual incidence of all‐cause mortality was 0.9/100 person‐years over a follow‐up period of 17,436.3 person‐years. Compared with patients who survived, those who died had a significantly higher pretreatment (89.3 vs. 67.4 U/L, p = 0.002) and Month‐6‐GGT levels (62.1 vs. 38.4 U/L, p < 0.001). The factors associated with all‐cause mortality included cirrhosis (hazard ratio [HR]/95% confidence interval [CI]: 2.66/1.92–3.70, p < 0.001), pretreatment GGT levels (HR/CI: 1.004/1.003–1.006, p < 0.001), alanine aminotransferase level (HR/CI: 0.996/0.994–0.998, p = 0.001), and age (HR/CI: 1.06/1.04–1.07, p < 0.001). Regarding liver‐related mortality, the independent factors included cirrhosis (HR/CI: 4.36/2.79–6.89, p < 0.001), pretreatment GGT levels (HR/CI: 1.006/1.004–1.008, p < 0.001), alanine aminotransferase level (HR/CI: 0.993/0.990–0.997, p = 0.001), age (HR/CI: 1.03/1.01–1.05, p < 0.001), and fatty liver disease (HR/CI: 0.30/0.15–0.59, p = 0.001). Pretreatment GGT levels were also independently predictive of non‐liver‐related mortality (HR/CI: 1.003/1.000–1.005, p = 0.03). The results remained consistent after excluding the patients with a history of alcohol use. A dose‐dependent manner of <25, 25–75, and >75 percentile of pretreatment GGT levels was observed with respect to the all‐cause mortality (trend p < 0.001). Pretreatment serum GGT levels predicted all‐cause, liver‐related, and non‐liver‐related mortality in patients with CHB treated with NAs.